2023
DOI: 10.1108/jeim-02-2022-0057
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical depiction of costing perspectives allied with the dynamics of processed food supply chain

Abstract: PurposeThis study aims to ground the assessment of the various costing perspectives associated with the dynamics of processed food supply chains (FSCs), for questing the avenues of profitability within a food processing enterprise.Design/methodology/approachThis study underpins the development of the relation hierarchical model, binding the cluster of the key costing enactors, with the various incurred costs in the food supply chain performance system. The developed model is seeded by the inputs gathered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In addition, research has shown that the transportation phase of food supply chains is the most difficult [ 16 ]. Regardless of how carefully items are packaged and maintained to avoid contamination, there is always an expense associated with the long-distance transportation and storage of food [ 17 ]. The price is typically paid by causing problems for the two most important indicators of sustainability, which are the economic (high prices for petroleum) and environmental systems (massive carbon footprint).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has shown that the transportation phase of food supply chains is the most difficult [ 16 ]. Regardless of how carefully items are packaged and maintained to avoid contamination, there is always an expense associated with the long-distance transportation and storage of food [ 17 ]. The price is typically paid by causing problems for the two most important indicators of sustainability, which are the economic (high prices for petroleum) and environmental systems (massive carbon footprint).…”
Section: Introductionmentioning
confidence: 99%